Does cybercrime affect brand loyalty to deposit money banks in Nigeria - Gbadebo, Adedeji Daniel (Edelweiss Applied Science and Technology, 2024)
The financial service industry, especially banking, has benefited greatly from the introduction of information technology. The technology has allowed them to offer a wide range of electronic banking services that have expanded scope of participants. This, however, has exposed the banks to cybercrime risk, posing serious threat to their survival. The study aimed to determine how the brand loyalty of the banks’ customers is affected by cybercrime associated to the use of e-banking platforms. The study used self-structured and administered questionnaires to gather primary data from 200 clients from (10) deposit money banks (DMBs) and examine the effects of cybercrime on customers brand loyalty. A regression analysis was performed to investigate the relationship between customer brand loyalty and the considered cybercrime activities. The finding identifies a strong inverse association between brand loyalty and financial losses brought on by cybercrime. Also, the evidence shows that card theft significantly reduces brand loyalty. The study further discovers that recurring security vulnerabilities significantly reduce brand loyalty and lastly, the paper demonstrates that the most notable adverse effect on brand loyalty was caused by identity theft. The study’s conclusions demonstrate a strong and unfavourable correlation between consumer brand loyalty and cybercrime. The article offers comprehensive recommendations, including policies, strategies, and interventions that show how cybercrime can be combated to reduce the risk of thefts in the banking sector.